A Two-Fluid Model Simulation of Vertical Gas-Solid Flow With a Multiphase Turbulence Model. (February 2023) - Singh, Bihara; Bergstrom, Donald J.
Highlights: There are two types of particle fluctuations in gas solid turbulent flows. The two particle fluctuations exhibit different behaviours. Mean phasic velocities predictions improve by dividing particle fluctuations. Abstract: A modified form of the Two-Fluid Model (TFM) incorporating a multiphase turbulence model is implemented in an in-house code for a downward gas-solid channel flow (Kulick et al., 1994 ). The TFM works on the principle of dividing the particle phase velocity fluctuations into spatially correlated and uncorrelated forms. The results from the modified TFM are compared with the experimental data as well as the predictions of a conventional TFM formulation. The difference between the two approaches in terms of the kinetic energy couplings of the two model formulations is discussed. The modified TFM was able to predict an enhanced gradient in the particle phase mean velocity close to the wall for a downward flow. The uncorrelated particle fluctuations showed a peak close to the wall and decreased toward the center of the channel, compared to a more uniform prediction by the conventional TFM. The correlated fluctuations showed a minimum value at the wall and increased to the same level as the uncorrelated fluctuations in the center of the channel. The prediction of the modified TFM for the solids volume fraction profile was closer to the experimental profile than the conventional model. Both TFM formulations were unable to capture the anisotropy associated with the fluid phase velocity fluctuations and its possible effects on the particle phase close to the wall.